The Role of Social Media Platforms in Enhancing English-Speaking Skill at Eleventh Grade Students of Senior High School - Khairun Nisya; Basikin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to explore the role of social media in supporting students’ English-speaking skills at SMAN 1 Suela. The study is grounded in the limited exposure to English-speaking environments in rural areas and students’ low confidence in daily English communication. Using a descriptive qualitative approach with a case study design, the research involved nine eleventh-grade students selected through purposive sampling. Data were collected through semi-structured interviews and classroom observations and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that students utilize social media platforms such as YouTube, TikTok, Instagram, and WhatsApp, with YouTube and TikTok being the most dominant for speaking practice. Students engage in activities including watching and imitating English videos, practicing pronunciation, creating video content, and expanding vocabulary. The use of social media contributes positively to vocabulary mastery, pronunciation improvement, and increased speaking confidence. However, challenges such as content distractions, limited internet access, and speaking anxiety remain significant barriers. Overall, social media serves as an accessible and contextual medium for informal English-speaking practice, particularly in rural educational settings.